Strategi Kepala Sekolah dalam Meningkatkan Kompetensi Profesional Guru Pada SMP Negeri 1 Belawang - Helmi Helmi; Ahmad Rudini; M. Ihsan Ramadhani; Nadya Huda; Nurul Huda Fitriani (Departement of Mathematics Education, 2023)
This study uses a descriptive method with a qualitative approach. Data collection techniques using observation, interviews, and documentation. The results of the study show that: Programs to improve the professional competence of SMP Negeri 1 Belawang teachers are: Curriculum development training such as preparing annual programs, semester programs, educational calendars, training in compiling syllabus, lesson plans (RPP). Improvement and enrichment program through MGMP. Improving the competence of educators (teachers) such as teacher certification training, computer training for teachers, holding internal teacher competency workshops. 2) The implementation of teacher professional competence improvement by the principal of SMP Negeri 1 Belawang, namely: Training in compiling a syllabus, and learning implementation plans (RPP). The improvement and enrichment program through the MGMP SMP Negeri 1 Belawang has attended trainings and upgrades, both internally and externally or outside of school. Improving the competence of educators (teachers) such as teacher certification training has been carried out, but the improvement as expected has not been achieved, computer training for teachers has been carried out but has not gone well, and held an internal teacher competency workshop, there has been an increase in understanding of the competencies that must be developed. have by the teacher. 3) The obstacles experienced by the principal in improving the professional competence of teachers at SMP Negeri 1 Belawang are the lack of support for facilities and infrastructure, the lack of awareness of teacher responsibilities, and the lack of support from the school committee and the community.